DENSITAS COLLEMBOLA DALAM TANAH PADA PERKEBUNAN KAKAO DI DESA POLEONRO KECAMATAN POLEANG TENGAH KABUPATEN BOMBANA SULAWESI TENGGARA - Sitti Wirdhana Ahmad; Amirullah Amirullah; Ranti Melkaresi (University of Halu Oleo, 2015)
ABSTRACT The aim of this research was to know the number of the family and the density of Collembolan found in the cocoa plantations in the village of Poleonro, Districts Poleang, Bombana, Southeast Sulawesi. This studied was of research exploration. The sampling done with the quadrant method is to install a number of quadrants in the specified path along 100 meters. Sampling was carried out above ground level and sampling under the ground level. The extration of Collembola was done used by Tullgreen Tunnel. The results showed that the cocoa in the village in cocoa plantations in the village poleonro namely Entomobrydae, Aronelidae, Tomoceridae, Willowsinae, Paronelidae, Oncopoduridae, Isotomidae, Cyphoderidae dan Arropalitidae, the density Collembola found as mus as 2 of the order that are divided into 9 families. Higest density on the family of Paronellidae (15,06%) and followed by family of Willowsinae and Arropalitidae (8,15%). Keywords: Density, Collembola, Cacao plantations, Village of Poleonro